2008
DOI: 10.4137/cmc.s876
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins in Cardiovascular Stress

Abstract: Heat shock proteins (HSPs) are primarily induced in response to stress stimuli. In cardiovascular diseases, HSPs are expressed pronouncedly and act to protect the cardiac tissue by inhibition of cellular apoptopic mechanisms. An ischemic condition preceded by angina prevents degeneration of tissue by 'ischemic preconditioning' in which HSPs produced in an earlier response have a protective effect towards subsequent cardiac injuries. This review highlights the manifestations of HSPs upon stress conditions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 116 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…HSPs are expressed pronouncedly in CVDs, which play a cardioprotective role by inhibiting apoptosis. 197 Numerous studies have shown that preinduction of HSPs by mild stress has a protective effect on a more severe stress, which is related to the amount of induced HSP. 198 In addition, overexpression of HSPs in cultured cardiomyocytes or transgenic animals or intact hearts using viral vectors also has a protective effect, which directly demonstrates the ability of HSPs to protect cardiac function.…”
Section: Heat Shock Proteins In Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPs are expressed pronouncedly in CVDs, which play a cardioprotective role by inhibiting apoptosis. 197 Numerous studies have shown that preinduction of HSPs by mild stress has a protective effect on a more severe stress, which is related to the amount of induced HSP. 198 In addition, overexpression of HSPs in cultured cardiomyocytes or transgenic animals or intact hearts using viral vectors also has a protective effect, which directly demonstrates the ability of HSPs to protect cardiac function.…”
Section: Heat Shock Proteins In Diseasesmentioning
confidence: 99%
“…On the one hand, HSPs are initially induced by stress stimuli. HSPs are expressed pronouncedly in CVDs, which play a cardioprotective role by inhibiting apoptosis 197 . Numerous studies have shown that preinduction of HSPs by mild stress has a protective effect on a more severe stress, which is related to the amount of induced HSP 198 .…”
Section: Heat Shock Proteins In Diseasesmentioning
confidence: 99%